Use of the spatial access ratio to measure geospatial access to emergency general surgery services in California. Issue 5 (May 2021) - McCrum, Marta L.; Wan, Neng; Lizotte, Steven L.; Han, Jiuying; Varghese, Thomas; Nirula, Raminder
Abstract : BACKGROUND: Emergency general surgery (EGS) encompasses a spectrum of time-sensitive and resource-intensive conditions, which require adequate and timely access to surgical care. Developing metrics to accurately quantify spatial access to care is critical for this field. We sought to evaluate the ability of the spatial access ratio (SPAR), which incorporates travel time, hospital capacity, and population demand in its ability to measure spatial access to EGS care and delineate disparities. METHODS: We constructed a geographic information science platform for EGS-capable hospitals in California and mapped population location, race, and socioeconomic characteristics. We compared the SPAR to the shortest travel time model in its ability to identify disparities in spatial access overall and for vulnerable populations. Reduced spatial access was defined as >60 minutes travel time or lowest three classes of SPAR. RESULTS: A total of 283 EGS-capable hospitals were identified, of which 142 (50%) had advanced resources. Using shortest travel time, only 166, 950 persons (0.4% of total population) experienced prolonged (>60 minutes) travel time to any EGS-capable hospital, which increased to 1.05 million (2.7%) for advanced-resource centers. Using SPAR, 11.5 million (29.5%) had reduced spatial access to any EGS hospital, and 13.9 million (35.7%) for advanced-resource centers. Rural residents had significantly decreased access for both overall and advanced EGS services when assessed by SPAR despite travel times within the 60-minute threshold. CONCLUSION: While travel time and SPAR showed similar overall geographic patterns of spatial access to EGS hospitals, SPAR identified a greater a greater proportion of the population as having limited access to care. Nearly one third of California residents experience reduced spatial access to EGS hospitals when assessed by SPAR. Metrics that incorporate measures of population demand and hospital capacity in addition to travel time may be useful when assessing spatial access to surgical services. LEVEL OF EVIDENCE: Cross-sectional study, level VI. Abstract : Supplemental digital content is available in the text.